2004
DOI: 10.1063/1.1682701
|View full text |Cite
|
Sign up to set email alerts
|

Electron emission through a multilayer planar nanostructured solid-state field-controlled emitter

Abstract: We have measured the field electron emission (FE) from a surface covered with two ultrathin layers of semiconductor, 4 nm GaN on 2 nm Al0.5Ga0.5N. The threshold field was 50 V/μm, with stable FE current densities up to 3×10−2 A/cm2. We have also measured the FE dependence with field and temperature and determine then an effective surface tunneling barrier ⩽0.5 eV, coexisting with an effective thermal activation energy of ∼0.85 eV. To interpret these experimental results, we propose a dual-barrier model, relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…Although, the FE mechanisms of the nanostructured materials are still under investigation, their physically confinement structures play an important role on it. Ultra-thin dielectric coatings on the emitter and quantum well FE structure show resonant tunnelling characteristics in their FE measurements attributed to two-dimensional electron confinement effect [1][2][3][4]. Furthermore, one-dimensional nanostructure such as carbon nanotubes and various types of nanowires achieve an emission current at extremely low applied electric fields (typically less than 5 V/µm) [5][6][7].…”
Section: Nanostructured Materials Not Only Have Unique Physical and Cmentioning
confidence: 99%
“…Although, the FE mechanisms of the nanostructured materials are still under investigation, their physically confinement structures play an important role on it. Ultra-thin dielectric coatings on the emitter and quantum well FE structure show resonant tunnelling characteristics in their FE measurements attributed to two-dimensional electron confinement effect [1][2][3][4]. Furthermore, one-dimensional nanostructure such as carbon nanotubes and various types of nanowires achieve an emission current at extremely low applied electric fields (typically less than 5 V/µm) [5][6][7].…”
Section: Nanostructured Materials Not Only Have Unique Physical and Cmentioning
confidence: 99%
“…The fully depleted sp 2 a-C layer could create electric fields much greater than the macroscopic field external to it. [12][13][14] Similar to the space charge induced band bending model for amorphous materials in which the Si substrate acts as the electron source, [12][13][14][15] Semet et al 5 and Wang et al 7 proposed an identical hypothesis for GaN based double layered structures. We postulate electron injection from Si into the sp 2 "well layer" through the 3 nm thick sp 3 layer by field penetration.…”
mentioning
confidence: 99%
“…1͑b͒ at the front positive end of the sample. According to the equation derived by Semet et al, 5 the space potential energy by the electrons accumulated in the first subenergy level ͑E 1 ͒ can be estimated as V SC = ͑ 0 /4 0 r ͕͒͑w / ͒ 2 sin 2͑x / w͒ + wx − x 2 ͖, where w is the thickness of the sp 2 layer and 0 is the space charge density ͑is proportional to the energy difference between the first and the second subenergy level͒. The E 2 − E 1 is calculated to be 0.45 eV ͑E 1 = 0.2 eV and E 2 = 0.65 eV͒ for the effective mass m * ϳ 0.06, r ϳ 4, and w = 3 nm which is further confirmed by modeling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a GaN surface roughened by H 2 -plasma treatment also exhibited electron emission in a relatively low electric field [8,9]. AlN nanotubes and GaN nano-structures were recently proposed to be good vacuum emitters [10,11]. However, only a few field emission studies of InN or In-rich-InGaN nanostructures have been reported [12].…”
Section: Introductionmentioning
confidence: 95%